A study of L. Van Beethoven’s Sonata Op. 31, No.1; Chopin’s Nocturne Op. 55, No. 2 and Ballade Op. 23; Ponce’s Prelude and Fugue on a theme by Handel; and Larregla’s ¡Viva Navarra! Jota de Concierto: historical, theoretical and stylistic implications - Vazquez Medrano, Oscar (Kansas State University, 2018)
The purpose of this Master’s report is to analyze the five-piano works at the author’s piano recital on April 8, 2018. The discussed pieces are Ludwig van Beethoven’s Sonata in G major Op. 31, No.1; Fryderyk Franciszek Chopin’s Nocturne Op. 55, No. 2 and Ballade in G minor, Op. 23; Manuel M. Ponce’s Prelude and Fugue on a theme by Handel; and Joaquín Larregla Urbieta’s ¡Viva Navarra! Jota de Concierto. The author approaches the analysis and study of the pieces from the historical, theoretical, and stylistic perspectives.
Keywords: Music; Piano; Ludwig van Beethoven; Fryderyk Francisek Chopin; Manuel M. Ponce; Joaquin Larregla Urbieta